Application of treated domestic sewage effluent on the quality indicators of an Oxisol cultivated with castor bean - Conceição dos Santos, Adailton; Luiz Boechat, Cácio; Cunha Saraiva, Paloma; Miranda de Santana Arauco, Adriana; Rocha, Felizardo Adenilson; da Silva Pinto Peixoto, Maria de Fátima (Revista Ceres, 2025)
In semi-arid regions of developing countries worldwide it is necessary to develop low cost technology methods to acquire new water supplies. The objective was to evaluate the changes in the attributes of soil quality irrigated with treated sewage effluent. The treatments consisted of applying treated sewage effluent (TSE) and underground well water (UWW) in the following proportions: E0% (chemical fertilization and UWW), E25% (25% TSE and 75% UWW), E50% (50% of TSE and UWW), E75% (75% TSE and 25% UWW) and E100% (100% TSE). The sodium content did not differ significantly among the treatments, but the sodium input diminished as the percentage of residuary water in the irrigation grew. There was a greater increment of microbial biomass carbon in the E25% treatment. On the other hand, although treatments E50% to E100% have a greater nutrient input, they were no different from control treatments performed with well water. Treated domestic sewage effluent at a proportion of 25% is a feasible alternative for castor bean irrigation, however it is necessary to monitor the possible changes in the soil attributes over successive crops. Microbial attributes can be used as a quick, good indicator of changes in soil quality.